Respondent Behavior in Panel Studies: A Case Study of the German Socio-Economic Panel (GSOEP) - Jörg-Peter Schräpler (Deutsches Institut für Wirtschaftsforschung (DIW), 2001)
In the past there have been many empirical studies dealing with the behavior of respondents in interview situations. Most of these refer to data from surveys and describe an interview situation where respondents and interviewer meet only once. The advantage of this study is the possibility of investigating both respondent behavior over a long period of time and the change in behavior in cases where the respondent meets the interviewer several times and becomes familiar with him. For thi study we use the database of the German Socio-Economic Panel (GSOEP). The GSOEP is a longitudinal survey containing socio-economic information on private households in the Federal Republic of Germany. It provides a wealth of methodological information about the survey methods utilized and the characteristics of the interviewer. The paper will focus on the analysis of response styles, item-nonresponse and social desirability. – – Die vorliegende Untersuchung beschäftigt sich mit dem Befragtenverhalten und Interviewereinflüssen im Sozio-oekonomischen Panel (GSOEP). Gegenüber vielen anderen Studien zu Befragten- und Interviewereffekten bezieht sich diese einfache Querschnitterhebung. So besteht die Möglichkeit, das Befragtenverhalten über einen längeren Zeitraum zu beobachten und auch Verhaltensänderungen zu analysieren, wenn Befragte und Interviewer im Zuge der Panellaufzeit mehrmals aufeinander treffen. Analysiert werden Befragteneffekte wie Response Styles, Item-Nonresponse und soziale Erwünschheit.
Keywords: C81; 330; Respondent behavior; Interviewer effects; Respondent effects; Panel analysis; Interview; Meinungsforschung; Panel; Schätzung; Deutschland